Perturbation of the Weighted T-Core-EP Inverse of Tensors Based on the T-Product (Communications in Mathematical Research, 2022)
In this paper, we extend the notion of the T-Schur decomposition tothe weighted T-core-EP decomposition. Next, the weighted T-core-EP inverseof rectangular tensors is defined by a system, and its existence and uniquenessare obtained. Furthermore, the perturbation of the weighted T-core-EP inverseis studied under several conditions, and the relevant examples are provided toverify the perturbation bounds of the weighted T-core-EP inverse of tensors.
Keywords: T-product; tensor; perturbation analysis; weighted T-core-EP inverse.